Cytokinesis in yeast meiosis depends on the regulated removal of Ssp1p from the prospore membrane - Maier, Peter; Finkbeiner, Martin G.; Taxis, Christof; Knop, Michael (The EMBO journal, 2007)
Intracellular budding is a developmentally regulated type of cell division common to many fungi and protists. In Saccaromyces cerevisiae, intracellular budding requires the de novo assembly of membranes, the prospore membranes (PSMs) and occurs during spore formation in meiosis. Ssp1p is a sporulation‐specific protein that has previously been shown to localize to secretory vesicles and to recruit the leading edge protein coat (LEP coat) proteins to the opening of the PSM. Here, we show that Ssp1p is a multidomain protein with distinct domains important for PI(4,5)P2 binding, binding to secretory vesicles and inhibition of vesicle fusion, interaction with LEP coat components and that it is subject to sumoylation and degradation. We found non‐essential roles for Ssp1p on the level of vesicle transport and an essential function of Ssp1p to regulate the opening of the PSM. Together, our results indicate that Ssp1p has a domain architecture that resembles to some extent the septin class of proteins, and that the regulated removal of Ssp1p from the PSM is the major step underlying cytokinesis in yeast sporulation.
Gesehen am 16.08.2017